Strategi Pemasaran Bakso Ikan Binaan IFAD di Kabupaten Merauke - Gumelar, Gesang Rizki; Widiastuti, Maria Magdalena Diana; Nahumury, Marthen A.I. (Musamus University, 2021)
This study aims to identify the factors that are strengths, weaknesses, opportunities and threats and to formulate appropriate strategies that can be used for marketingIFAD fish balls using the SWOT matrix, IE matrix and QSPM matrix. The researchwas carried out in 4 processing groups assisted by IFAD located in Maro Village andSamkai Village, Merauke District, Merauke Regency.The results obtained from this study are market penetration with strategy specifications based on the QSPM matrix, namely maximizing the number ofproducts marketed by utilizing existing facilities and infrastructure such asoptimizing commercial houses, packaging houses, vegetable stalls, stalls, shops andsupermarkets as marketing place, with a total alternative score of 12.82